Implementation of the Islamic Religious Education Curriculum at Alam Jomin Elementary School - Fahmi Arifudin, Yadi; Maulana, Azis; Aisyah, Siti; Rakasiwi, Sinta (Lembaga Penelitian dan Pendidikan Mandala, 2024)
One important component in the world of education is the curriculum, the curriculum can be defined as a program aimed at and designed for students. In its true definition, Islamic religious education can be said to be an educational system that can show human life in accordance with Islamic ideology, so that they can achieve peace and prosperity throughout their lives.The Indonesian Natural School is a school that was founded in order to produce efforts to develop an education system that is carried out in the open air so that students receive direct learning from all living creatures in the natural surroundings.